SOSIOLOGI LEMBAGA PENDIDIKAN MADRASAH IBTIDAIYAH: STUDI TENTANG KESENJANGAN DIGITAL (DIGITAL DIVIDE) DALAM PEMBELAJARAN DARING DAN LURING PASCA PANDEMI - Restu Darma; Muhammad Hanif (PREDESTINASI, 2026)
This study aims to analyze the post-COVID-19 digital divide phenomenon and the role of the digitalization process in transforming the conventional learning system into a modern one at MIN 1 Banyumas. This study employs a qualitative approach with a descriptive method. Data collection techniques included in-depth interviews, direct observation, and document analysis of informants selected through snowball sampling. The findings indicate that MIN 1 Banyumas successfully overcame these obstacles through strategic adaptation, namely collaborating with Amikom University to develop independent platforms such as Madrasah Digital, CBT, and B-link. This initiative was supported by regular digitalization training for teachers held every three weeks and the "Guru Keliling" (Mobile Teacher) program to educate parents. The integration of these digital media has proven to continue effectively into the post-pandemic era for visualizing complex materials and conducting interactive assessments via Quizizz.Keywords: Digital Divide; Madrasah Ibtidaiyah; Online Learning; Offline Learning; Sociology of Education.